2006
DOI: 10.1073/pnas.0603249103
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid two-component system protein of a prominent human gut symbiont couples glycan sensing in vivo to carbohydrate metabolism

Abstract: Bacteroides thetaiotaomicron is a prominent member of our normal adult intestinal microbial community and a useful model for studying the foundations of human-bacterial mutualism in our densely populated distal gut microbiota. A central question is how members of this microbiota sense nutrients and implement an appropriate metabolic response. B. thetaiotaomicron contains a large number of glycoside hydrolases not represented in our own proteome, plus a markedly expanded collection of hybrid twocomponent system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 16 publications
5
129
0
7
Order By: Relevance
“…Typically, expression of one of the capsular polysaccharide synthesis loci (cps3) is upregulated when polysaccharides are scarce. In a mutant deficient in BT3172, expression of cps3 is increased even in the presence of a medium rich in polysaccharides, suggesting that BT3172 is important for the bacterium to properly interpret its nutrient landscape in terms of adequate supply of polysaccharides (263).…”
Section: Environmental Sensing Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, expression of one of the capsular polysaccharide synthesis loci (cps3) is upregulated when polysaccharides are scarce. In a mutant deficient in BT3172, expression of cps3 is increased even in the presence of a medium rich in polysaccharides, suggesting that BT3172 is important for the bacterium to properly interpret its nutrient landscape in terms of adequate supply of polysaccharides (263).…”
Section: Environmental Sensing Systemsmentioning
confidence: 99%
“…In one system, nutrient sensing is coupled to regulation of monosaccharide metabolism (263). BT3172 belongs to this family of proteins, and its expression is regulated by polysaccharides in the environment.…”
Section: Environmental Sensing Systemsmentioning
confidence: 99%
“…Frequently, such processes are mediated by two-component sensor proteins, involving a usually membrane-bound sensor protein, and a response regulator. A set of 32 unusual hybrid periplasmicsensing two-component sensor histidine kinases were discovered in the human gut symbiont Bacteroides thetaiotaomicron (2). These hybrid two-component sensor systems (HTCS) were unusual in that they incorporated all of the domains found in the classical two-component system into a single polypeptide (3).…”
mentioning
confidence: 99%
“…These hybrid two-component sensor systems (HTCS) were unusual in that they incorporated all of the domains found in the classical two-component system into a single polypeptide (3). Sonnenburg et al (2) hypothesized that the HTCS proteins were involved in how these microbiota sense diverse nutrients and implement an appropriate metabolic response, and showed that loss of one of these HTCS proteins, BT3172, reduced glycotic pathway activity. They also found that the sensor domains of the HTCS proteins were less highly conserved than their intracellular signaling domains, suggesting that the HTCS proteins have diversified to respond to a variety of signals while conserving their means of intracellular signal transduction.…”
mentioning
confidence: 99%
“…For example, bifidobacteria have developed intricate mechanisms to inhabit the mucus layer of intestinal tracts of mammals, where many other microorganisms cannot persist 30,52,88,93,98,124 . It has been known that bifidobacteria have acquired the ability to adhere to the mucosal barrier system of the intestinal tract, while developing the resistance to bactericidal bile 35 .…”
Section: Striking Similarities Between Sake and Beer Spoilage Labmentioning
confidence: 99%